Are we using enough library e-services Investigating the level of library e-services usage among students / Mohamad Rahimi Mohamad Rosman and Nurfatihah S Baharuddin - Mohamad Rosman, Mohamad Rahimi; S Baharuddin, Nurfatihah (2021)
Utilization of library e-services are a major concern, especially among practitioners. The emergence of Novel Coronavirus 2019 (COVID-19) has increased the dependency towards library e-services, such as online databases, electronic books, electronic journals, etc. Moreover, the movement control order (MCO), as well as the rising cases of COVID-19, has shifted the library, as well as librarian responsibility towards the online delivery of services. In the meantime, students rely heavily on library e-services to complete their works. However, not much is known regarding the utilization level of library e-services in the aftermath of COVID-19, especially regarding the perceived barriers. Therefore, the study aims to investigate the utilization level of library e-services in the aftermath of COVID-19 pandemic. A quantitative study was conducted; a total of 192 responses were recorded and analysed. Data were analysed using central tendency based on mean, standard deviation, and median. Findings show that the resultant central tendency of the study shows that the level of library e-services usage among undergraduate students at Universiti Teknologi MARA Cawangan Kelantan is at a moderate level, with the mean value of 4.66